SISTEM INFORMASI TERPADU UNTUK MENJALANKAN SISTEM BISNIS TERINTEGRASI - Yetti Afrida Indra (Dinamika Akuntansi Keuangan dan Perbankan, 2015)
When for the first time the concept of Integrated Information System in the early 1990s introduced, thousands of companies are racing to implement the new paradigm of looking at business strategy tersebut.Hasilnya surprisingly enough, in the sense of quite a lot of companies that ultimately managed to significantly improve their performance significant and transforming itself into a world-class corporation. Seeing this, a number of executives in developed countries are trying to apply this concept to his company with the ultimate goal to improve the quality of the performance of institutions, particularly in meeting the challenges of the globalization era .From the results obtained shown that the paradigm of Integrated Information System that is used is a stone stepping effective in helping to run the company's business.Keywords: integrated information systems, business